Head Kinematics and Shoulder Biomechanics in Shoulder Impacts Similar to Pedestrian Crashes-A THUMS Study - Paas, Ruth; Davidsson, Johan; Brolin, Karin (Traffic injury prevention, 2015)
Objective: Head injuries account for the largest percentage of fatalities among pedestrians in car crashes. To prevent or mitigate such injuries, safety systems that reduce head linear and rotational acceleration should be introduced. Human body models (HBMs) are valuable safety system evaluation tools for assessing both head injury risk and head kinematics prior to head contact. This article aims to evaluate the suitability of the Total Human Model for Safety (THUMS) version 4.0 for studying shoulder impacts, similar to pedestrian crashes, investigating head, spine, and shoulder kinematics as well as shoulder biomechanics. Methods: Shoulder impact experiments including volunteers and postmortem human subjects (PMHSs) were simulated with THUMS. Head linear and angular and vertebral linear displacements of THUMS were compared with volunteers and shoulder deflections with both volunteers and PMHSs. A parameter variation study was conducted to assess head response to shoulder impacts, by varying shoulder posture and impact directions mimicking shoulder-to-vehicle contacts. Functional biomechanics literature was compared with THUMS responses in view of pedestrian-like shoulder impacts. Results: THUMS head linear displacement compared better with tensed than with relaxed volunteers. Head lateral rotation was comparable with volunteer responses up to 120 ms; head twist was greater in THUMS than in the volunteers. The THUMS spine appeared to be stiffer than in the volunteers. Shoulder deflections were smaller than in the relaxed volunteers but matched the PMHSs. Raised shoulder postures decreased the THUMS shoulder deflections and increased head lateral displacements. When the impactor surface orientation or the impact velocity angle was changed from lateral to superolateral, THUMS head lateral displacement decreased. THUMS scapula and clavicle kinematics compared well with previous experimental studies. The shoulder impact conditions influenced the scapula motion over the thorax, which had considerable effect on upper torso and head kinematics. The clavicle primarily acted as a guide for the scapula. In the PMHS experiments, it took 20 ms from first impactor-to-shoulder contact to head response, indicating that shoulder impacts in pedestrian crashes may influence head kinematics during head impact. Conclusions: THUMS is generally suitable for studying head linear kinematics and head lateral rotation in shoulder impacts similar to pedestrian crashes and for studying shoulder girdle biomechanics. Head twist and spine stiffness were more pronounced than in the volunteers. The results have identified the need for additional volunteer shoulder impact testing, mimicking pedestrian crashes, as well as the need to address shoulder impacts in full-scale pedestrian experiments.